Pengaruh Media Sosial dalam Penyelesaian Sengketa Ketatanegaraan Terkait Tantangan dan Peluang di Era Demokrasi Digital - Alim, Yanti; Olivia, Dhea; Moonti, Roy Marthen (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
Social media has changed the way people communicate and share information, opening up great opportunities as well as challenges such as hoaxes and polarization. In Indonesia, these platforms have become important spaces for public discussion, especially in politics. Wise management is needed for social media to support transparency, accountability and democracy. The purpose of this study is to analyze the role of social media in constitutional dispute resolution, identify challenges that arise, and provide recommendations for wise management so that social media can support transparency, accountability, and democratic principles. This research uses a normative method. Social media has a major role in constitutional disputes, both as a tool for information dissemination and a space for public discussion. On the one hand, social media helps transparency, participation, and community mobilization in constitutional issues. However, on the other hand, it also poses challenges such as disinformation, hoaxes, and political polarization that can escalate conflicts. Regulation and supervision are needed to address the misuse of social media without compromising freedom of expression. Digital literacy education is also important to encourage responsible use of social media, so that it can be a tool to support democracy and peaceful dispute resolution. Social media can worsen the political situation through hoaxes and hate speech. Therefore, clear regulations are needed to prevent abuse without reducing freedom of speech. Policy reforms that balance surveillance and freedom of expression are important, with collaboration between the government, platforms and communities to create a safe digital space. Digital literacy also needs to be improved so that people can sort out information and support political stability.